Prospek Kerjasama Negara-Negara Asean dalam Pengendalian Pencemaran Udara Lintas Batas - Muhammad Basarah (Jurnal Hukum IUS QUIA IUSTUM, 2000)
Air pollution particularly in developing countries is not considered as a terrifying mater. The nuclear experiment in Brazil, For example, reminds us that all attempt to prevent air pollution should be made as soon as possible. The awareness of the developing countries about legal responsibility to commit various activities in their own countries does not cause air pollution and environmental defect; and it cannot be hesitated. The involvementof the developing countries in handling environmental matters is proof.